The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/00268976.2015.1007107
|View full text |Cite
|
Sign up to set email alerts
|

On exchange coupling and bonding in the Gd2@C80 and Gd2@C79N endohedral dimetallo-fullerenes

Abstract: A series of computational experiments performed with various methods belonging to wave-function and density functional theories approaches the issue of bonding regime and exchange coupling in the title compounds. Gd 2 @C 80 is computed with a very weak exchange coupling, the sign depending on the method, while Gd 2 @C 79 N has resulted with a strong coupling and ferromagnetic ground state, irrespective of the computational approach. The multi-configuration calculation and broken symmetry estimation are yieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 40 publications
1
31
1
1
Order By: Relevance
“…31 and Supplementary Note 10). Similar large values were predicted recently for Gd 2 @C 79 N (refs 35, 36) and the EPR study of the latter revealed a S =15/2 ground state, which points to the ferromagnetic coupling of all spins in the [Gd 3+ – e –Gd 3+ ] system34. These parameters can be compared with the [Gd 3+ –N 2 3− –Gd 3+ ] complex with a radical bridge, in which Gd ions are antiferromagnetically coupled to the electron spin of the N 2 3− bridge with the j Gd, e value of −27 cm −1 (ref.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…31 and Supplementary Note 10). Similar large values were predicted recently for Gd 2 @C 79 N (refs 35, 36) and the EPR study of the latter revealed a S =15/2 ground state, which points to the ferromagnetic coupling of all spins in the [Gd 3+ – e –Gd 3+ ] system34. These parameters can be compared with the [Gd 3+ –N 2 3− –Gd 3+ ] complex with a radical bridge, in which Gd ions are antiferromagnetically coupled to the electron spin of the N 2 3− bridge with the j Gd, e value of −27 cm −1 (ref.…”
Section: Resultssupporting
confidence: 91%
“…A single-electron M–M bond has been also stabilized by a substitution of one carbon atom by nitrogen, giving azafullerenes M 2 @C 79 N (M=Y, Gd, Tb)3334. Computational studies predicted a large ferromagnetic coupling of Gd ions in Gd 2 @C 79 N (refs 35, 36) and unusual magnetic properties in Dy 2 @C 79 N (ref. 35).…”
mentioning
confidence: 99%
“…They were computed in the LFDFT algorithm using the following non-empirical parameters: F k (ff) and z 4f ( Table 2); F k (fd), G k (fd), z 5d and D(fd) ( Table 6); and B k q 's parameters ( Table 5). The transitions from the initial 4f 7 ( 8 S 7/2 ) state to the final 4f 6 5d 1 are electric dipole-allowed, with the calculation of the electric dipole transition moments obtained from eqn (15). The oscillator strength for the zero phonon lines between the ground state 8 S 7/2 of 4f 7 and the final states of 4f 6 5d 1 are calculated and represented in Fig.…”
Section: The 4f 7 -4f 6 5d 1 Transitionsmentioning
confidence: 99%
“…We note also that the ligand−field splitting of the Eu 5d orbitals is 30 times larger than that obtained for Eu 4f, the Eu 5d being more available for bonding properties. 15,57 The calculated parentage coefficients of Eu(η 9 -C 9 H 9 ) 2 from Eu 5d are relatively weak (see Table 5). Namely, we obtained circa 43% for 5d σ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%